Global Economic Prospects, June 2018 : The Turning of the Tide? - World Bank Group (Washington, DC: World Bank, 2018)
Published semiannually, Global Economic Prospects includes analysis of topical policy challenges faced by developing countries. Global activity is firming broadly as expected. Manufacturing and trade are picking up, confidence is improving, and international financing conditions remain benign. Global growth is projected to strengthen in 2018-19, in line with January forecasts. In emerging market and developing economies (EMDEs), growth is predicted to recover in 2017-19, as obstacles to growth in commodity exporters diminish amid moderately rising commodity prices, and activity in commodity importers remains robust. Risks to the global outlook remain tilted to the downside. These include increased trade protectionism; elevated economic policy uncertainty; the possibility of financial market disruptions; and, over the longer term, weaker potential growth. A policy priority for EMDEs is to rebuild monetary and fiscal space that could be drawn on were such risks to materialize. Over the longer term, structural policies that support investment and trade are critical to boost EMDE productivity and potential growth.